Entrepreneurial competencies and performance of informal Micro‐Enterprises in Malaysia - Abdullah Al- Mamun; Noorshella Che Nawi; Perasna A/P Subramaniam; Noor Raihani Zainol (2015)
Introduction • An informal economy consists of economic activities that occur outside of the formal institutional boundaries. • Informal economy is characterized by low entrance requirements in terms of capital and qualified workers, small scale operations, and labor intensive methods of production and technology. • Oven, informal businesses are small and family-‐run or run by a single entrepreneur.